Pituitary dysfunction in patients with ANCA associated vasculitis: prevalence, presentation, and outcomes. (June 2020) - Li, Chunjia; Zou, Yu; Lu, Xin; Wang, Guochun; Shu, Xiaoming
Background: The antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) are rare multisystem autoimmune diseases characterized by inflammatory cell infiltration causing necrosis of small blood vessels. Pituitary involvement in AAV is poorly described. This study aimed to describe the prevalence, clinical characteristics, and outcomes of pituitary involvement in patients with AAV. Methods: A total of 150 patients diagnosed with AAV and hospitalized in the China–Japan Friendship Hospital between 2009 and 2019 were enrolled in this retrospective study. Patients diagnosed with pituitary involvement in AAV were selected for inclusion. Results: Three patients (2%) were identified with pituitary involvement. Two patients had positive ANCA titers, one with proteinase 3 positive and one with myeloperoxidase positive antibodies. Pituitary dysfunction presented as an initial symptom in one patient and developed over the course of the diseases in the other two patients. All three patients had abnormal hormones. Among them, two patients had an enlarged pituitary, shown by magnetic resonance images (MRIs), and one patient had a normal sized pituitary, shown by MRI, but presented with increased linear radioactivity uptake in the pituitary fossa by positron emission tomography-computed tomography. All patients were treated with corticosteroid and immunosuppressive therapy. Both pituitary dysfunction and vasculitis were in remission. Conclusion: Pituitary involvement is uncommon in AAV and it can occur at any point during AAV. The main clinical manifestations are central diabetes insipidus and panhypopituitarism. Immunosuppressive therapy could significantly alleviate clinical symptoms as well as pituitary imaging.